2020
DOI: 10.1103/physreve.101.062707
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic equations of state for the liquid crystalline phase behavior of hard rods

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 50 publications
1
38
0
Order By: Relevance
“…In this model, the colloidal rods cannot penetrate each other and do not interact otherwise. Computer simulations , revealed that dispersions of hard spherocylinders can assume isotropic (I), nematic (N), smectic-A (SmA), AAA, and ABC phase states (see Figure for a sketch of these phase states). , The thermodynamically preferred phase state depends on the concentration and length–diameter aspect ratio. In both the isotropic and nematic phases, there is no positional order, but in the nematic phase, the rods assume a preferred orientation.…”
Section: Introductionmentioning
confidence: 99%
“…In this model, the colloidal rods cannot penetrate each other and do not interact otherwise. Computer simulations , revealed that dispersions of hard spherocylinders can assume isotropic (I), nematic (N), smectic-A (SmA), AAA, and ABC phase states (see Figure for a sketch of these phase states). , The thermodynamically preferred phase state depends on the concentration and length–diameter aspect ratio. In both the isotropic and nematic phases, there is no positional order, but in the nematic phase, the rods assume a preferred orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Using a Gaussian approximation for the distribution of rod angles with respect to the nematic director, one can construct algebraic equations of state [37]. Given that PL theory tends to be more accurate for weakly anisotropic rods while SPT has proven more reliable for long rods, we employ a straightforward sigmoidal interpolation procedure in order to accurately cover the full range of aspect ratios [40]. We emphasize that the observed phase behavior is robust and is not qualitatively affected by details of the rod-polymer model (see Fig.…”
mentioning
confidence: 99%
“…Phase behavior of hard spherocylinders as a function of rod volume fraction η and aspect ratio D=L from both theory (solid curves)[40] and simulation (data points)[14]. The stable phases include the isotropic (I), nematic (N), smectic A (SmA), AAA crystal, and ABC crystal phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…where Λ is the De Broglie wavelength. For the range of reservoir concentrations used in this work it is expected that the rod-like particles do not form a nematic phase but behave as a fluid 22,43 . Therefore, the scaled particle theory (SPT) result for a fluid dispersion of hard spherocylinders 44 is used for the osmotic pressure in the reservoir:…”
Section: A Semi-grand Potentialmentioning
confidence: 99%